Pembuatan Teks Editor Sederhana Menggunakan Fasilitas Enkripsi dekrepsi pada Visual Studio 2005 - Putro, Cahyanto Tunggal; Rahayu, Cicilia Puji; -, Budi Nugroho (Siscode, 2013)
Data or information exchange trough computer is often performed, one of them by using flash disk. However flash disk can also be used to steal data or information owned. Therefore, an effort needs to be performed to protect data from possibility of data stealing, one of them is by changing data which want to be code of data that can be opened if there is a same pass word used. This text publication disccuses how Â to make application which can change original text to be text of code with facility of encryption decryption on visual studio 2005. Encryption is kind of way to gain security of data by changing original text to cipher text. Data which is not made in encryption is called plaintext, while which can be made in encryption is called chipper text to return to plaintext again is called decryption. The result of encryption which appeared alike text which is made in code and the result of decryption is a like original text. For our security which has been made in encryption which can also be protected by password or key word. Keywords : Encryption, Decryption, Code, Password.